المساهمة الجنائية في التشريع الإسلامي والتشريع الجنائي الجزائري (جريمة خطف الأطفال نموذجا )-دراسة مقارنة - صولي, حسين; كريكر, طارق; غطاس, نور الدين (University of eloued جامعة الوادي, 2022)
"في معرض الحديث عن بحثنا هذا والمتمثل في المساهمة الجنائية في التشريع الجنائي الإسلامي والتشريع الجنائي الجزائري والذي قمنا فيه بالحديث عن مفهوم المساهمة الجنائية وأركانها وأنواعها في كلا التشريعين. كما قمنا بالتطرق إلى دراسة نموذج من نماذج المساهمة الجنائية، والمتمثل في جريمة اختطاف الأطفال، هذا الأخير الذي يمكن أن يتم باستعمال القوة والعنف مع المخطوف، أو بدونهما عن طريق الحيلة أو الاستدراج لنقله من مكان تواجده وحجزه لمدة زمنية، كما عرجنا على أركانها في كلا التشريعين والمتمثل في الركن الشرعي، الركن المادي و الركن المعنوي. وختمنا البحث بالحديث عن الجزاء المترتب عن جريمة خطف الأطفال في الشريعة الإسلامية ( القتل، الصلب، القطع من خلاف، قطع اليدين، النفي) ، أما المشرع الجزائري فقد أوقع الجزاء على الفاعل الأصلي والشريك على حد سواء ( القتل بالإعدام، السجن المؤبد والسجن المؤقت،) إضافة إلى العقوبات التبعية والتكميلية. ثم الخاتمة لهذا الموضوع . ""In this research, we discuss the criminal contribution in the Islamic criminal legislation and the Algerian criminal legislation. In the first chapter, we define the criminal contribution which means the case of many criminals when they commit the same crime whatever is the degree of the contribution of each one is a result of a collective crime. In addition, we deal with secondary elements of the criminal contribution in the Islamic and the Algerian legislations respectively in which they agree on the unity of the crime with multiple criminals. Furthermore, we deal with the types of the criminal contributions in the two legislations; in the Islamic legislation, the direct contribution (through agreement, provoking or helping the criminals). Whereas in the Algerian legislation, we have two types: the physical original and the moral original (ancillary contribution). In the second chapter, we deal with a sample of a criminal contribution which is children kidnapping. In the first part, we define ""kidnapping"" which can be used forcibly or violently or without both of them; or by tricking and luring the victim to take him/ her away to detain him for a period of time. As well as, we discuss the pillars of the criminal contribution in the two legislations which are: the legal corner, the phisical corner, and the moral corner.
مذكرة الماستر
Keywords: المساهمة -الجنائية -الاشتراك-الاختطاف; the criminal legislation - the Islamic - tha Algerian - contribution - criminal- participation- kidnapping